Baghdadi Method as Alternative System for Learning Qur'an at MT. Nur Hikmah Mampang Depok City - Maharani, Dewi; Septiani, Safitri; Febriani, Amanda Sahla; Sari, Yeasy Agustina (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2021)
This research is motivated by the fact that there are still many people who are unable to read the Qur'an because they have not found t easy method of learning in reading Qur'an.. To overcome this problem, efforts from various parties are needed. For this reason, the teacher must ensure the right method and approach. Because the right method will guarantee the achievement of a greater and more comprehensive level of success. This research aims to improve the ability to read the Qur'an, introduce harakat, and the preparation of hijaiyah letters based on makharijul letters. The results of this research were obtained from observations, assessments that were tried twice, and interviews with children. Based on the analysis of information on children's activities above, it can be concluded that the dominant activity carried out is learning with the Baghdadi method, which is 30%, on the contrary, based on interviews, the Baghdadi method is very appropriate and interesting to use. So it can be concluded that this method is very interesting and supports the learning process of children. The results of the last test showed an increase in understanding of reading the Qur'an so that it reached the predetermined success indicators. Keywords: Baghdadi Method, Learning Qur’an, System of Learning Qur’an